Health-related quality of life during bosutinib (SKI-606) therapy in patients with advanced chronic myeloid leukemia after imatinib failure. (2nd August 2016) - Whiteley, Jennifer; Reisman, Arlene; Shapiro, Mark; Cortes, JorgeE.; Cella, David
Abstract: Objectives: The tyrosine kinase inhibitor (TKI) bosutinib has demonstrated activity in patients with advanced phase chronic myeloid leukemia (CML), but effects on health-related quality of life (HRQoL) remain unexplored. This study evaluated HRQoL in advanced CML patients receiving bosutinib in an ongoing phase 2 study following resistance or intolerance to prior imatinib therapy. Methods: This analysis included data from 76 accelerated-phase (AP) and 64 blast-phase (BP) patients resistant/intolerant to prior imatinib with or without prior exposure to other TKIs. Patient-reported HRQoL assessments completed at baseline; weeks 4, 8, and 12; every 12 weeks thereafter; and at treatment completion included the Functional Assessment of Cancer Therapy–Leukemia (FACT-Leu); general health status was assessed using the 5-item EuroQol (EQ-5D) instrument and a visual analog scale (VAS). Results: HRQoL at baseline was somewhat worse in BP versus AP CML patients. There was a significant improvement in the mean FACT-Leu Total scale at weeks 24, 36, and 48 in AP CML patients and at weeks 4, 8, 12, 24, 36, 48, and 96 in BP CML patients compared with baseline. EQ-5D Utility scores were stable throughout treatment in AP CML patients but significantly improved versus baseline in BP CML patients at weeks 4, 8, 12, and 36. Mean VAS scores were significantly improved at weeks 8, 36, and 48 in AP CML patients and at weeks 4, 8, 12, 24, 36, and 96 in BP CML patients. The lack of a comparison group limits attribution of improvements in HRQoL specifically to bosutinib treatment; potential bias due to non-ignorable dropout may limit the ability to generalize these findings to situations where durations of therapy exceed the 96-week follow-up duration of the present study. Conclusion: These findings suggest that bosutinib therapy is associated with improved HRQoL in advanced phase CML patients. Clinical trial registration: NCT00261846.